Simulations of Hypervelocity Impacts into Graphite. (2015) - Hébert, D.; Seisson, G.; Bertron, I.; Hallo, L.; Chevalier, J.-M.; Thessieux, C.; Guillet, F.; Boustie, M.; Berthe, L.
Abstract: This paper presents numerical simulations of hypervelocity impacts of 0.5-mm steel spheres into graphite, for velocities ranging between 1100 and 4500 m/s. Experiments have evidenced a non-monotonic evolution of the projectile penetration depth, along with the trapping of the projectile below the crater surface. Using numerical simulations and simple constitutive relations, we show how our experimental results can be related to both materials mechanical properties. We take advantage of the succession of physical mechanisms to build a step by step procedure and identify thresholds of yield and spall strength that allow a first restitution of the experimental results. These threshold values for the steel projectile were found to be consistent with the literature. As regards the graphite target, the yield strength has also been identified, and we propose to model its dependence with pressure through a linear relation. Comparisons between experiments and simulations are presented and discussed. Despite some difference at the highest impact velocities, the overall trend is well reproduced, which suggests that our results could be used as a starting point for further studies with more complex models.